2003
DOI: 10.1093/dnares/10.5.203
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Sequence of Seventy-nine New Transcripts Expressed in Hemocytes of Ciona intestinalis, Three of Which May Be Involved in Characteristic Cell-cell Communication

Abstract: Ascidian is a useful experimental animal for studying body planning principles and host defense mechanisms employed by the phylum chordata. Toward this goal, genome and cDNA/EST projects of Ciona intestinalis have been undertaken. Using cDNAs and ESTs derived from Ciona hemocytes, we identified 79 possible hemocyte-preferential transcripts and determined the cDNA sequence of each clone. The amino acid sequence of each encoded polypeptide was predicted as well. Among these cDNAs, we identified three transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Recent reports of a genome-wide analysis of C. intestinalis have provided a comprehensive picture of immune-related genes (Dehal et al 2002;Azumi et al 2003;Terajima et al 2003) and shown that IL1 genes are not contained in the genome, whereas the recorded C-type lectin and galectin genes can be expressed by hemocytes from untreated ascidians Azumi et al 2003). The inflammatory reaction in the tunic of C. intestinalis (Parrinello 1981;Parrinello et al 1984aParrinello et al , b, 1990) is a suitable model for the examination of inducible humoral cytokine-like factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of a genome-wide analysis of C. intestinalis have provided a comprehensive picture of immune-related genes (Dehal et al 2002;Azumi et al 2003;Terajima et al 2003) and shown that IL1 genes are not contained in the genome, whereas the recorded C-type lectin and galectin genes can be expressed by hemocytes from untreated ascidians Azumi et al 2003). The inflammatory reaction in the tunic of C. intestinalis (Parrinello 1981;Parrinello et al 1984aParrinello et al , b, 1990) is a suitable model for the examination of inducible humoral cytokine-like factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ascidian IL-17R gene was identified from its genome and by a cDNA/EST study, showing similarity with that of mouse IL-17R (probability, E-11). There is a signal peptide domain in the N-terminal and a transmembrane domain in the central portion of the predicted protein [69]. Its structure is similar with that of mammalian IL-17R.…”
Section: Interleukin-17 Receptorsmentioning
confidence: 96%
“…In invertebrates, the IL-17 receptor gene was isolated from ascidian C. intestinalis [69] and sea urchin S. purpuratus [54]. Ascidian IL-17R gene was identified from its genome and by a cDNA/EST study, showing similarity with that of mouse IL-17R (probability, E-11).…”
Section: Interleukin-17 Receptorsmentioning
confidence: 99%
“…Despite the common opinion that invertebrate cytokines share no homologies with their vertebrate counterparts (138, 139), putative genes for IL1 and TNF receptors were identified in the Ciona genome (44, 61). A gene for a TNFα homolog, the transcription of which increases in Ciona hemocytes after LPS injection in the body wall, was also cloned (11, 140): it probably exerts a role in recruiting hemocytes to the inflamed area (141).…”
Section: Humoral Defensive Repertoirementioning
confidence: 99%
“…Ascidian hemocytes, involved in immune responses (immunocytes), represent a relevant fraction of circulating hemocytes (32), synthesize most of the pattern-recognition receptors (Table 2) and actively transcribe genes required for immune defense (60, 61): they include phagocytes and cytotoxic cells. Phagocytes are wandering, spreading cells that actively move toward foreign cells or particles and ingest them.…”
Section: The Sites Of Immune Responsesmentioning
confidence: 99%